Reporting physical activity in minutes not bouts: findings from a survey in Australia - Lucy Corbett; Erika Bohn‐Goldbaum; Melanie Crane; Lina Engelen (Elsevier, 2021)
Abstract Objective: Physical activity has been commonly measured as time spent in bouts of at least 10 minutes, however, each minute of physical activity achieved in a day is now regarded as beneficial. This study aims to compare differences in total time spent walking in a week to time spent walking in 10‐minute bouts over the same seven‐day period. Methods: Two self‐reported measures of time spent walking were compared: one using time‐constrained bouts and the other using total minutes. The first measure comes from the validated Active Australia Survey and reports walking in bouts of 10min or more, the second measure reports total estimated time spent walking. Results: Data from 4,582 university participants in a census‐styled survey were analysed. When comparing the reported minutes of walking in either 10‐minute bouts or total minutes, more walking occurs in short bursts with a difference of 117min/week (p<0.001). Conclusions: This result shows more walking is reported across a week in short bursts of less than 10 minutes. Implications for public health: To monitor trends and evaluate physical activity interventions, reliable and valid measures of physical activity are necessary. Our result questions the usefulness of reporting bouted‐walking as a measure which accurately captures population behaviour.